The Effect of Birth Cohort on Well-Being - Sutin, Angelina R.; Terracciano, Antonio; Milaneschi, Yuri; An, Yang; Ferrucci, Luigi; Zonderman, Alan B. (Psychological Science, 2013)
In the present research, we examined the effects of age, cohort, and time of measurement on well-being across adulthood. Cross-sectional and longitudinal analyses of two independent samples—one with more than 10,000 repeated assessments across 30 years (mean assessments per participant = 4.44, SD = 3.47) and one with nationally representative data—suggested that well-being declines with age. This decline, however, reversed when we controlled for birth cohort. That is, once we accounted for the fact that older cohorts had lower levels of well-being, all cohorts increased in well-being with age relative to their own baseline. Participants tested more recently had higher well-being, but time of measurement, unlike cohort, did not change the shape of the trajectory. Although well-being increased with age for everyone, cohorts that lived through the economic challenges of the early 20th century had lower well-being than those born during more prosperous times.